2015
DOI: 10.4315/0362-028x.jfp-15-146
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Rapid Knowledge Synthesis and Transfer Approach To Assess the Microbial Safety of Low-Moisture Foods

Abstract: Low-moisture foods (LMF) are increasingly implicated in outbreaks of foodborne illness resulting in a significant public health burden. To inform the development of a new Codex Alimentarius code of hygienic practice for LMF, we applied a rapid knowledge synthesis and transfer approach to review global research on the burden of illness, prevalence, and interventions to control nine selected microbial hazards in eight categories of LMF. Knowledge synthesis methods included an integrated scoping review (search st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 61 publications
(83 reference statements)
0
8
0
1
Order By: Relevance
“…23 https://doi.org/10.22201/fesz.23958723e.2020.0.274 Análisis fisicoquímico del polvo de pericarpio Los bajos contenidos de humedad y a w , obtenidos del polvo de pericarpio del mango ʻAtaulfoʼ maduro (Cuadro 1), facilitan el manejo y transporte para su posible uso en el procesamiento u obtención de otros productos alimenticios. Un valor de a w < 0.85 y contenido de humedad < 6% incrementan el almacenamiento de los productos alimenticios, por la reducción del crecimiento microbiano debido al bajo contenido de agua (Barbosa, Fontana, Schmidt & Labuza, 2008;Young et al 2015).…”
Section: Resultados Y Discusiónunclassified
“…23 https://doi.org/10.22201/fesz.23958723e.2020.0.274 Análisis fisicoquímico del polvo de pericarpio Los bajos contenidos de humedad y a w , obtenidos del polvo de pericarpio del mango ʻAtaulfoʼ maduro (Cuadro 1), facilitan el manejo y transporte para su posible uso en el procesamiento u obtención de otros productos alimenticios. Un valor de a w < 0.85 y contenido de humedad < 6% incrementan el almacenamiento de los productos alimenticios, por la reducción del crecimiento microbiano debido al bajo contenido de agua (Barbosa, Fontana, Schmidt & Labuza, 2008;Young et al 2015).…”
Section: Resultados Y Discusiónunclassified
“…The following pathogenic microorganisms were identified in BC and IC and in outbreaks where breakfast cereals were the culprit foods: Salmonella spp. [37,71,72] and Bacillus cereus [36,37,61,73,74]. In the ASAE's Database, no data concerning the occurrence of pathogenic microorganisms in cereal-based products was registered.…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella is the most frequently implicated pathogen in reported enteric illness outbreaks linked to low-moisture foods [21,24,25]. In a recent review of worldwide low-moisture food outbreaks, Salmonella was found to have caused 45% of the outbreaks [6]. Additionally, Salmonella can survive in low-moisture foods such as black pepper, peanut butter, and powdered products for more than a year under normal storage conditions [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Nontyphoidal S. enterica is the second most common cause of foodborne disease outbreaks in the United States, and poultry and fresh produce consumption are well-established outbreak vehicles [4,5]. Low-moisture foods, including spices and seasonings; dried protein products such as dried egg or dried milk; and seeds have been increasingly implicated as the source of foodborne salmonellosis outbreaks [6][7][8].…”
mentioning
confidence: 99%